2014
DOI: 10.1097/pgp.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Effects of Medroxyprogesterone Acetate on Endometrioid Endometrial Adenocarcinoma

Abstract: Purpose Progestins have been used in the treatment of recurrent endometrial adenocarcinoma for almost 50 years. Some endometrial carcinomas respond to hormonal therapy, but the mechanism of action remains incompletely known. We wished to determine the efficacy of progestins to induce a histologic response in endometrioid carcinomas and explore its effects on histologic and immunohistochemical measures of growth and cell death. Methods The Gynecologic Oncology Group initiated a study of 75 women with endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…Of the 10 patients that were included in the study, most demonstrated a significant reduction in PR protein expression post-IUD insertion as compared to pre-insertion (Figure 2A–C). Levels of the progesterone receptor isoform B (PRB) were also markedly decreased in post-treatment biopsies (Figure 2A–C), consistent with a previous report demonstrating downregulation in response to progestin-based therapy [20]. Pearson correlation analysis demonstrated that post-IUD insertion expression of ER significantly correlated with PRB (Figure 2D), in line with the reported relationship between hormone receptors in endometrial tumors [29].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Of the 10 patients that were included in the study, most demonstrated a significant reduction in PR protein expression post-IUD insertion as compared to pre-insertion (Figure 2A–C). Levels of the progesterone receptor isoform B (PRB) were also markedly decreased in post-treatment biopsies (Figure 2A–C), consistent with a previous report demonstrating downregulation in response to progestin-based therapy [20]. Pearson correlation analysis demonstrated that post-IUD insertion expression of ER significantly correlated with PRB (Figure 2D), in line with the reported relationship between hormone receptors in endometrial tumors [29].…”
Section: Resultssupporting
confidence: 90%
“…In general, PR and PRB levels decrease in response to progestin-IUD therapy, as has been previously demonstrated in the non-therapeutic study of the histologic impact of medroxyprogesterone acetate in patients scheduled for hysterectomy for endometrial cancer (GOG 211) [20]. The mechanism underlying short term hormone receptor down-regulation in response to ligand has been well documented: ligand causes receptor phosphorylation – the necessary precursor for transcriptional activation – while at the same time serving as a signal for receptor ubiquitination and destruction in the proteasome.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The authors reported a 64% par al response rate and one complete response among 59 women. 28 Interes ngly, GOG-0211 illustrated a downregula on of progesterone receptor a er exposure to medroxyprogesterone. In preclinical models, progesterone receptor downregula on is thought to result from promoter CpG hypermethyla on and gene silencing.…”
Section: Practical Applicationsmentioning
confidence: 99%